AUTOMATION OF THE PROCESS OF PLANNING THE ACTIVITIES OF SCIENTIFIC AND TEACHING EMPLOYEES OF HIGHER EDUCATION INSTITUTIONS OF THE SECURITY AND DEFENSE FORCES - Sukonko, Serhii; Poberezhnyi, Andriy; Lun, Oleksii (Honor and Law, 2023)
In accordance with the Law "On Higher Education", the working time of a scientific and pedagogical employee of a higher education institution is divided into educational, methodical, scientific and organizational work. The recommended list of activities for the mentioned works is determined by the order of the Ministry of Education and Science, and the time norms for these activities are determined by the institution of higher education. In addition to the above, institutions of higher education of the security and defense forces use departmental guidelines during the process of organizing the educational process and planning the activities of scientific and pedagogical workers. Therefore, the planning of activities of scientific and pedagogical workers of higher education institutions of the security and defense forces has certain differences from civilian institutions of higher education. Working time measures for a year by each scientific and pedagogical employee of a higher education institution in the areas of methodical, scientific and organizational work are carried out personally on the basis of the Regulation of the higher education institution on planning and accounting for the working time (load) of a scientific and pedagogical employee and taking into account the hours that have been determined guidance for educational work. The planned activities of each scientific and pedagogical employee are approved by the head (head) of the department. In turn, based on the planned events for the year, scientific and pedagogical workers plan their working hours for each month of the initial year. All the specified measures are reflected in the sections of the individual plan of the scientific and pedagogical worker and are controlled by the head (head) of the department. During the specified control, it is necessary to check: − compliance of time allocation for educational, methodical, scientific and organizational work with the requirements of the governing documents; − the correctness of the time allocation for the activities of the specified works; − compliance of events planned for the month and for the year; − compliance of the amount of planned hours per month with hours per year for each event; − the total amount of working hours planned by the scientific and pedagogical employee for a month with hours that are determined by the norms of the duration of working hours for the current year; − timeliness of implementation of planned measures for each half-year and for the year as a whole and other. Since the number of planned activities for each direction of work (educational, methodical, scientific and organizational) for each scientific and pedagogical employee is different, the number of hours for the implementation of these activities is also different, so for quality control of the implementation of activities by each scientific and pedagogical employee, the head of the department needs to spend a lot a lot of time. In addition, it should be noted that even following a certain method of planning the working time of a scientific and pedagogical worker, sometimes they make mistakes in planning due to taking into account a large number of factors when planning their work for the year and directly for each month. Therefore, in order to facilitate the work of a scientific and pedagogical employee, during the planning of events, and the head of the department, during the control of the implementation of these events, the authors automated the method of planning the working time of a scientific and pedagogical employee of a higher education institution of the security and defense forces at the expense of the developed planning program and accounting of the workload of scientific and pedagogical workers of the institution of higher education of the security and defense forces. This program allows you to simplify the work of scientific and pedagogical workers during the planning of working hours by semesters and as a whole for the year, as well as for each month by types of work, namely: educational, scientific, methodical and organizational, taking into account the requirements of departmental management documents from the organization planning the activities of scientific and pedagogical workers. In addition, the program makes it possible to generate all the necessary information in Excel format, which makes it easier for the heads (heads) of departments to control their subordinates regarding the planning and implementation of specified activities.